#loveyourshelfie: Mills & Boon books and how to find them - Fletcher, Lisa; McAlister, Jodi; Temple, Kurt; Williams, Kathleen (Mémoires du livre / Studies in Book Culture, 2019)
“Mills & Boon” has become shorthand for “trashy” entertainment, yet little is known about how the books are treated materially in their circulation. This article reports on a project that followed the material lives and afterlives of 50 Australian-authored novels published by Harlequin Mills & Boon between 1996 and 2016. We analyze visual and textual data about these books collected via social media to explore uses and values attached to category romance. First, we show that the books’ ongoing circulation is due both to their publishers’ practices, and to the behaviours of genre insiders. Second, we note that most participants demonstrated “genre competence” and genre-based sociality, confirming the highly networked nature of the romance “genre world.” Third, we find that category romance is routinely shelved apart from other books, explicitly marking them as distinctive. Finally, we argue that “shelfies” of romance collections undercut notions of trash by reframing them as treasure.